2020
DOI: 10.1016/j.jpubeco.2020.104238
|View full text |Cite
|
Sign up to set email alerts
|

Labor demand in the time of COVID-19: Evidence from vacancy postings and UI claims

Abstract: We thank Dan Restuccia, Matt Sigelman, and Bledi Taska for providing the Burning Glass Technologies data, as well as Shiwani Chitroda, Nathan Maves-Moore and Fan Xia for excellent research assistance. This research was undertaken, in part, thanks to funding from the Canada Research Chairs program. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
168
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(189 citation statements)
references
References 16 publications
14
168
1
6
Order By: Relevance
“…In April 2020, the U.S. economy lost 20 million jobs and, each week, millions of workers filed new unemployment insurance claims. As we showed in (Forsythe et al [2020]), the future looked * We thank Dan Restuccia, Matt Sigelman, and Bledi Taska for providing the Burning Glass Technologies data, as well as Anahid Bauer, Shiwani Chitroda, and Nathan Maves-Moore for excellent research assistance. This research was undertaken, in part, thanks to funding from the Canada Research Chairs program.…”
Section: Introductionmentioning
confidence: 95%
“…In April 2020, the U.S. economy lost 20 million jobs and, each week, millions of workers filed new unemployment insurance claims. As we showed in (Forsythe et al [2020]), the future looked * We thank Dan Restuccia, Matt Sigelman, and Bledi Taska for providing the Burning Glass Technologies data, as well as Anahid Bauer, Shiwani Chitroda, and Nathan Maves-Moore for excellent research assistance. This research was undertaken, in part, thanks to funding from the Canada Research Chairs program.…”
Section: Introductionmentioning
confidence: 95%
“…Researchers in the United States have examined how non-pharmaceutical interventions have impacted unemployment insurance, employment, or store client traffic. Some research suggests that lockdowns explain a small share of the total economic activity decline [22,[30][31][32]. Others [24,33,34] have found that lockdowns play a relevant role in explaining the drop in economic activity.…”
Section: Introductionmentioning
confidence: 99%
“…See e.g. Adams-Prassl et al (2020); Alstadsaeter et al (2020); Borjas and Cassidy (2020); Dingel and Neiman (2020); Fairlie et al (2020); Montenovo et al (2020); Yasenov (2020)7 However,Forsythe et al (2020) also show that the crisis had a strong short-term impact on job vacancies and UI claims in all industries and for most occupations in the US.…”
mentioning
confidence: 99%